Post-racial solidarity and the possibilities of national shame after Christchurch - Ghumkhor, Sahar (Criminological encounters, 2023)
Emotions do not simply exist and are expressed based on individual experiences but emerge in bodies, spaces, and histories. Emotions are key to the practice of foreclosing history and consolidating national memory. The article brings literature on emotions into conversation with findings from focus groups and interviews with Muslim community leaders and organisers in Auckland, Christchurch, Melbourne and Sydney on grief and grievance after the 2019 attacks on two mosques in Christchurch. Guided by these findings the article contends that a ‘postracial solidarity’ emerged after the attacks that centred national grief, love (aroha) and compassion, stifling Muslim grief and grievances. It explores the possibilities of shame as an emotion that decentres or brings into question, what David Theo Goldberg calls the "racial state" (2002). The article explores how shame can bring about conditions for more meaningful recognition of racial harm and justice.